1973
DOI: 10.1042/cs0450785
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethinyloestradiol on Calcium and Phosphorus Metabolism of Post-Menopausal Women with Primary Hyperparathyroidism

Abstract: 1. Eight post-menopausal women with primary hyperparathyroidism were given ethinyloestradiol (0.05 mg daily) and the effects on calcium and phosphorus metabolism were observed.2. In every patient ethinyloestradiol produced a fall in fasting plasma and urine calcium. Calcium balance improved in seven patients on treatment and there was a significant fall in 24 h urine calcium in all eight patients; however, there was no consistent change in net or true absorption of calcium.3. Ethinyloestradiol produced a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…This observation supports the general concept that estrogen inhibits bone resorption in vivo (2,3,22,24,28,(35)(36)(37)(38), although in vitro studies showed OVX rats that were infused with 17,3E2 (C and F). Fourteen days after ovariectomy, rats were infused with PBS or 1 nM 1713E2 into the metaphyseal region of the femur for 8 days, 24 ,ul/day.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This observation supports the general concept that estrogen inhibits bone resorption in vivo (2,3,22,24,28,(35)(36)(37)(38), although in vitro studies showed OVX rats that were infused with 17,3E2 (C and F). Fourteen days after ovariectomy, rats were infused with PBS or 1 nM 1713E2 into the metaphyseal region of the femur for 8 days, 24 ,ul/day.…”
Section: Discussionsupporting
confidence: 69%
“…A major unanswered question is whether estrogen action on bone in vivo is direct or indirect (4,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). It has been suggested that in vivo estrogen promotes the systemic production of growth factors, so-called estromedins, or the removal of growth inhibitors, estrocolyons, elsewhere in the body (42).…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogens and androgens rather than progesterone have been shown to affect the skeletal metabolism during its maturation and the bone loss which accompanies ageing (Silberberg & Silberberg, 1971;Dequeker, 1975). Most studies have supported the view that oestrogens and androgens act as inhibitors of bone resorption in vivo (Cmess & Hong, 1976;Gallagher & Wilkinson, 1973). In vitro studies are not conclusive (Atkins, Zanelly, Peacock & Nordin, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…More frequent administration of parathyroid hormone may be needed to increase intestinal calcium and phosphate absorption. Patients with primary hyperparathyroidism have increased phosphate absorption (56,57), whereas the acute administration of parathyroid hormone to normal subjects does not alter radiophosphorus absorption (58).…”
Section: Discussionmentioning
confidence: 99%